Comparative Analysis of Financial Performance in Banking Companies in ASEAN-5 Countries before and during the Covid-19 Pandemic (Lighthouse Publishing, 2022)
The Covid-19 pandemic had a very bad impact on the world economy, which caused global economic growth to experience a decline of 3%, while developing countries were the hardest hit, with an average economic decline of 4%, some even more than 6.5 %. This study aims to analyze the financial performance of banks in ASEAN-5 countries between before and during the Covid-19 Pandemic. The method of comparing banking financial performance is by using the CAMEL method with a research sample of banking sub-sector companies listed on the stock exchange in each ASEAN-5 country. The results showed that there were significant differences in banking performance in ASEAN-5 countries, where two variables, namely the non-performing loan and operational efficiency ratio variable as a proxy for Assets and Earnings respectively did not have a significant difference. In general, the difference in bank health performance was due to the Covid-19 pandemic; many banks implemented policies that were adaptive to developments in the Covid-19 case, such as credit restructuring. On the other hand, the risk of bad credit has also increased due to the economic recession which has caused people to be unable to finance their obligations.